PAM50 subtyping and ROR score add long-term prognostic information in premenopausal breast cancer patients - Christine Lundgren; Pär-Ola Bendahl; Sarah E. Church; Maria Ekholm; Mårten Fernö; Carina Forsare; Ute Krüger; Bo Nordenskjöld; Olle Stål; Lisa Rydén (npj Breast Cancer, 2022)
Abstract PAM50 intrinsic subtyping and risk of recurrence (ROR) score are approved for risk profiling in postmenopausal women. We aimed to examine their long-term prognostic value in terms of breast cancer-free interval (BCFi) and overall survival (OS) (n = 437) in premenopausal women randomised to 2 years of tamoxifen versus no systemic treatment irrespective of hormone-receptor status. Intrinsic subtyping added independent prognostic information in patients with oestrogen receptor-positive/human epidermal growth factor 2-negative tumours for BCFi and OS after maximum follow-up (overall P-value 0.02 and 0.006, respectively) and those with high versus low ROR had worse prognosis (maximum follow-up: hazard ratio (HR)BCFi: 1.70, P = 0.04). The prognostic information by ROR was similar regarding OS and in multivariable analysis. These results support that PAM50 subtyping and ROR score provide long-term prognostic information in premenopausal women. Moreover, tamoxifen reduced the incidence of breast cancer events only in patients with Luminal APAM50 tumours (0–10 years: HRBCFi(Luminal A): 0.41, HRBCFi(Luminal B): 1.19, P interaction = 0.02). Trial registration: This trial is registered in the ISRCTN database, trial ID: ISRCTN12474687.